2021
DOI: 10.3389/fpsyg.2021.716220
|View full text |Cite
|
Sign up to set email alerts
|

The Interplay Between Affective Processing and Sense of Agency During Action Regulation: A Review

Abstract: Sense of agency is the feeling of being in control of one's actions and their perceivable effects. Most previous research identified cognitive or sensory determinants of agency experience. However, it has been proposed that sense of agency is also bound to the processing of affective information. For example, during goal-directed actions or instrumental learning we often rely on positive feedback (e.g., rewards) or negative feedback (e.g., error messages) to determine our level of control over the current task… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(5 citation statements)
references
References 146 publications
(221 reference statements)
0
5
0
Order By: Relevance
“…Recent work has directly assessed the influence of affective manipulations on implicit and explicit measures of SOA (Kaiser et al 2021). It was found that affective manipulations have a much more consistent impact on explicit than implicit measures: Positive compared to negative action outcomes increase the explicit feeling of agency.…”
Section: Multi Methods Approach For Sense Of Agencymentioning
confidence: 99%
See 1 more Smart Citation
“…Recent work has directly assessed the influence of affective manipulations on implicit and explicit measures of SOA (Kaiser et al 2021). It was found that affective manipulations have a much more consistent impact on explicit than implicit measures: Positive compared to negative action outcomes increase the explicit feeling of agency.…”
Section: Multi Methods Approach For Sense Of Agencymentioning
confidence: 99%
“…To investigate this, a body of research has focused on negative action outcomes, such as fearful or angry human vocalisations, which reduce the sense of agency over the committed action compared to either positive or neutral outcomes (Barlas et al 2018;Christensen et al 2016;Gentsch et al 2015;Takahata et al 2012;Yoshie & Haggard 2013), (Moreton et al 2017, for contrary findings). It should be noted that results were dependent on predictability and anticipation of action outcome (for a review, Kaiser et al 2021). From this, Christensen et al (2019) suggest that a negative emotional state during action performance might cause a reduction in the sense of control over one's actions and their external outcomes as well.…”
Section: Moderating Factors For the Sense Of Agencymentioning
confidence: 99%
“…and was displayed independently of the participant's performance. This manipulation was implemented with the intention to increase the SoA, as many studies show that positive feedback (even if decoupled from performance) should increase a post-hoc judgement of the SoA indicating a self-serving bias [Herman and Tsakiris 2020; Kaiser et al 2021;Nataraj et al 2020;Oishi et al 2018].…”
Section: Task and Designmentioning
confidence: 99%
“…A number of studies have been successful in manipulating the SoA and testing the extent of its malleability [Braun et al 2018]. The degree to which SoA varies depends on an array of factors such as temporal proximity between action and effect [Haggard and Tsakiris 2009], feedback and affective states (e.g., an increase in SoA for positive action outcomes [Kaiser et al 2021]), task difficulty, and social context (e.g., coercion and taking orders are shown to decrease the SoA [Haggard 2017]).…”
mentioning
confidence: 99%
“…Personality adjustment is defined by the adults' ability to master developmental changes that may arise in biological, psychological and interpersonal domains of their lives to attain, preserve or recover subjective well‐being and quality of life (Staudinger & Kessler, 2009). Adults' motivation for adjustment goals reflects the desire to nurture meaningful activities and relationships that facilitate the allocation of personal and environmental resources in the acquisition of a flexible repertoire of coping strategies designed to manage normative developmental tasks and effectively respond to societies' norms and expectations (Bauer et al, 2015; Hoyt et al, 2020; Kaiser et al, 2021). This successful management of a developmental‐contextual world can be measured having as a subjective criterion the satisfaction with life (as an indicator of subjective well‐being) and as objective criteria of personality adjustment, longevity and competence (Staudinger & Bowen, 2010).…”
Section: Introductionmentioning
confidence: 99%